Amazonian terrestrial water balance inferred from satellite-observed water vapor isotopes - Mingjie Shi (Nature Communications, 2022)
The evolution of the Amazon forest is tightly coupled to its terrestrial water balance. Here, the authors show that forest biomass changes in the Amazon are a driver of the spatiotemporal variation of evapotranspiration, and such changes could have a larger impact on water availability in the dry regions (southern, eastern) of the Amazon.